Adsorption and Photodegradation of Molasses Wastewater using TiO2-ZnO Hybrid Nanocatalysts Supported on Activated Carbon and Silica - Otieno, Benton Onyango (Vaal University of Technology, 2017)
There is an increasing use of composite materials in photo-catalysed remediation of wastes such as molasses wastewater (MWW), which is characterised by high organic load and a dark brown colour caused by biorecalcitrant melanoidin compounds. This study was carried out to determine the photocatalytic efficiency of a TiO2-ZnO hybrid supported onto activated carbon (AC) and silica for the remediation of MWW. Immobilisation of ZnO onto synthesised TiO2 formed TiO2-ZnO, which was then supported onto AC and silica, to give TiO2-ZnO/AC and TiO2-ZnO/Silica composites, respectively. Powder X-ray diffraction (XRD), scanning electron microscopy (SEM), Energy-dispersive X-ray (EDX) and Fourier Transform Infrared (FTIR) spectroscopies, and transmission electron microscopy (TEM), revealed the successful hybridisation of TiO2 and ZnO, and the subsequent support of the hybrid onto AC and silica. Thermal stability of the synthesised composite catalysts was studied by differential thermal analysis (DTA) and thermal gravimetric analysis (TGA). Photoluminescence (PL) spectroscopy further revealed a restrained electron-hole pair recombination resulting from both the successful formation of a heterojunction in the hybrid, and the introduction of electron accepting AC support. Introduction of a silica support on the other hand increased the rate of recombination resulting in reduced quantum efficiency of the TiO2-ZnO/Silica composite, hence AC was adopted as the ideal support material for this study. Photodegradation was monitored in terms of colour and total organic carbon (TOC) reductions, and nitrate formation. It was observed that the TiO2-ZnO hybrid, due to its desirable optical properties, had better activity than the respective oxides (TiO2 and ZnO). On supporting the hybrid onto AC, both adsorption and photocatalytic activities were further enhanced with improved overall colour removal of 86% from 68%. Photodegradation followed pseudo-first order rection model, with the rate constant (𝑘𝑎𝑝𝑝) decreasing from 0.0701 to 0.0436 min-1 with increased MWW initial concentration from 3000 to 6000 ppm. Formation of nitrates confirmed a reductive pathway for the degradation of melanoidins. The UV-photodegradation process was found to be 33-fold less energy intensive for colour reduction as compared to TOC reduction, with energy demands of 35 and 1183 kWh/m3, respectively. Sorption of MWW onto TiO2-ZnO/AC fitted well with the Freundlich isotherm and were found to be endothermic in nature with physisorption being the rate determining step. An optimum pH of 5 for the degradation process was determined. The robustness of the composite TiO2-ZnO/AC photocatalyst was revealed by its high reusability up to four cycles.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Adsorption; Photodegradation; Wastewater; Photocatalytic activities; Photocatalyst; TiO2-ZnO; Activated carbon; Dissertations, Academic -- South Africa.; Water reuse.; Water--Purification.; Water--Purification--Photocatalysis.; Carbon, Activated.